TO THE ISSUE OF PREVENTION OF NSAID-ASSOCIATED GASTROENTEROPATHY - Мартынова, Нина Андреевна (Medicine in Kuzbass, 2016)
Subject of the study: Experimental NSAID-associated gastroenteropathy.Objective of the study – the search for the means of prevention of NSAID-gastroenteropathy.Research methods. NSAID-gastroenteropathy was simulated by the application of indomethacin to the skin of rats. We researched the effectiveness of verospiron, omeprazole, famotidine, hydrochlorothiazide and furosemide for the prevention of NSAID-gastroenteropathy.Basic results. Indomethacin fivefold when applied to the skin of rats caused the development of gastroenteropathy and 100 % death of the animals. Verospiron added to the animal feed (dose 25 mg/kg) simultaneously with the application of indomethacin to the skin prevents the development of gastroenteropathy and death of the animals. Omeprazole, famotidine, hydrochlorothiazide and furosemide have been ineffective for the prevention of gastroenteropathy caused by indomethacin.Conclusions. The high efficiency of verospiron as a means for preventing gastroenteropathy when applying the indomethacin to the skin is shown.
Keywords: NSAID-gastroenteropathy; gastroenteritis protector; indomethacin; verospiron